A content analysis approach toward the human capital components: the state-of-the-art. (28th December 2020) - Roshani, Kosar; Mojallal, Zahra; Owlia, Mohammad Saleh
This study involves a structured review of peer-reviewed articles in the domain of intellectual capital categorisation, and in particular human capital (HC). The aim of this paper is to provide a framework of all the components that have so far been recognised as HC components. Sixty-five models were identified in the HC field (as a part of intellectual capital or independently), and the timeline of these studies was drawn accordingly. To achieve the study purpose, the content analysis method has been used on the qualitative data available in the models and a HC conceptual model was developed. Through this model, the main dimensions and components of HC were introduced. In many cases, the identification of HC components is difficult and some components may be missed. This paper provides a comprehensive and applicable list for any industry or organisation through identifying all value drivers and HC components.